Adoption of ICT among SMEs : case study of computer-based company / Karmidawati Kartimin - Kartimin, Karmidawati (2006)
SMEs development in Malaysia is given commitment from the Malaysian Government by implemented various policies and strategies. The purpose is to enhance the growth of the businesses sector across the entire value chain and clusterbased industrial developments with integrated approach to the development of industrial areas and opportunities for growth of SMEs. On the other hand, Malaysian Government encourages investing in ICT globalization as another approach to growth in business by SMEs. Therefore the adoption is a key element to securing economic growth. It is thus not surprising that technology policy stresses the importance of the SMEs' capacity to absorb and successfully apply ICT. From this perspective, understanding the benefits and constraints will enable ICT adoption. The case study of the adoption of ICT among SMEs in Kuala Lumpur has been handled. The research is set within the literature of ICTs adoption. Its present a description of the 30 SMEs from computer-based company situated within the locality together with the vision for economic growth. Structured interview is conducted to identify what benefits and constraints of adoption ICT for SMEs at this area. In effect, the benefits will lead more active use of ICT meanwhile the constraints will lead inactive use of ICT. The survey also include identifying the usage of ICT by SMEs like the purpose of usage, factors derive usage and types of ICT usage.